Examining the Relationship Between Quality Assurance Practices and Teachers’ Commitment in Public Primary Schools in Gusau Local Government Area, Zamfara State - Saliha Yahaya; Rabiatu Musa Mafara (Penerbit Hellow Pustaka, 2026)
This study examined the relationship between quality assurance practices and teachers’ commitment in public primary schools in Gusau Local Government Area, Zamfara State. The study was guided by three objectives which focused on the extent of implementation of quality assurance practices, the level of teachers’ commitment, and the relationship between both variables. A descriptive survey research design was adopted. The population of the study comprised 1,324 respondents, from which a sample of 291 was selected using the Research Advisors (2006) table. Data were collected using a structured questionnaire validated by experts and tested for reliability, yielding a coefficient of 0.93. Descriptive statistics of mean and standard deviation were used to answer research questions, while Pearson Product Moment Correlation was used to test the hypothesis at 0.05 level of significance. The findings revealed that quality assurance practices are moderately implemented in public primary schools in the study area. It was also found that teachers’ commitment is relatively high in terms of attendance, punctuality, and instructional responsibilities. Furthermore, a significant positive relationship was established between quality assurance practices and teachers’ commitment (r = 0.62, p < 0.05). The study concluded that effective implementation of quality assurance practices enhances teachers’ commitment in public primary schools. It was recommended that supervision, monitoring, and evaluation mechanisms should be strengthened to further improve teachers’ commitment and school effectiveness.